Seasonality and Oldowan behavioral variability in East Africa. Issue 164 (March 2022) - Linares-Matás, Gonzalo J.; Clark, James
Abstract: The extent, nature, and temporality of early hominin food procurement strategies have been subject to extensive debate. In this article, we examine evidence for the seasonal scheduling of resource procurement and technological investment in the Oldowan, starting with an evaluation of the seasonal signature of underground storage organs, freshwater resources, and terrestrial animal resources in extant primates and modern human hunter-gatherer populations. Subsequently, we use the mortality profiles, taxonomic composition, and taphonomy of the bovid assemblages at Kanjera South (Homa Peninsula, Kenya) and FLK-Zinj (Olduvai Gorge, Tanzania) to illustrate the behavioral flexibility of Oldowan hominins, who were targeting different seasonally vulnerable demographics. In terms of the lithic assemblages, the specific opportunities and constraints afforded by dry season subsistence at FLK-Zinj may have disincentivized lithic investment, resulting in a more expedient toolkit for fast and effective carcass processing. This may have been reinforced by raw material site provisioning during a relatively prolonged seasonal occupation, reducing pressures on the reduction and curation of lithic implements. In contrast, wet season plant abundance would have offered a predictable set of high-quality resources associated with low levels of competition and reduced search times, in the context of perhaps greater seasonal mobility and consequently shorter occupations. These factors appear to have fostered technological investment to reduce resource handling costs at Kanjera South, facilitated by more consistent net returns and enhanced planning of lithic deployment throughout the landscape. We subsequently discuss the seasonality of freshwater resources in Oldowan procurement strategies, focusing on FwJj20 (Koobi Fora, Kenya). Although more analytical studies with representative sample sizes are needed, we argue that interassemblage differences evidence the ability of Oldowan hominins to adapt to seasonal constraints and opportunities in resource exploitation.